Barong Landung as Inspiration for the Creation of Painting Works - Prayoga, I Made Adi Putra; Kondra, I Wayan; Budiarta, I Dewa Putu Gede (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2023)
The classic painting art of Wayang Kamasan has a distinctive depiction of figures, coloring techniques and complementary ornaments so that it has been preserved and maintained until now. In Bali there is also Barong Landung which has a historical background and interesting characteristics. The creation of this work and writing aims to find the author's unique painting style which is inspired by the figure of Wayang Kamasan by raising the topic of Barong Landung. The method used in the process of creating this work of art is the method of writing by Hawkins, which includes the stages of exploration, improvisation, and forming. The results of this activity are in accordance with the stages carried out, namely (1) during the exploration stage, ideas and relevant studies are generated regarding the works created; (2) the improvisation stage resulted in a sketch on a sketchbook; and (3) the formation stage produced six paintings according to the plot or history of Barong Landung